The Truncated Fourier Operator. General Results - Katsnelson, V.; Machluf, R. (Журнал математической физики, анализа, геометрии, 2012)
Let F be the one dimensional Fourier-Plancherel operator and E be a subset of the real axis. The truncated Fourier operator is the operator FE of the form FE = PEFPE, where (PEx)(t) = 1IE(t)x(t), and 1IE(t) is the indicator function of the set E. In the presented work, the basic properties of the operator FE according to the set E are discussed. Пусть F - одномерный оператор Фурье-Планшереля, а E - подмножество действительной оси. Усеченным оператором Фурье называется оператор FE вида FE = PEFPE, где (PEx)(t) = 1IE(t)x(t), а 1IE(t) - индикатор множества E. Обсуждаются основные свойства оператора FE, соответствующего множеству E.